Developing of a small power turbine recovering energy from low enthalpy steams or waste gases: Design, building and experimental measurements. (June 2018) - Barbarelli, S.; Florio, G.; Scornaienchi, N.M.
Highlights: A new tangential flow 5 deflectors small turbine prototype is introduced. It was designed as an improvement of a previous 3-deflectors prototype. The design methodology has been confirmed by measurements at the test rig. The prototype can work efficiently in a wide set of operating conditions. Its rotational speed is lower with respect to analogous small turbines. Abstract: For several years the authors have been involved in the design and building of tangential flow small turbines with rotating channel and tangential feeding nozzle. Their non-typical configuration allows better recovery of energy from gases or steams otherwise discarded, characterized by low temperature and low enthalpy. In this paper the authors introduce a new 5 deflector prototype, improved with respect to a previous version and fed by air. The prototype was measured to a 70 kW test rig, equipped with an electronic data acquisition system for automated measurement management. The experimental approach has been useful to analyse the working. First results show that the overall efficiency of the new turbine prototype is higher with respect to the first one. Moreover, the performances are comparable with the other small-power configurations, but the rotational speed is significantly reduced.